Advances in the study of Wellens syndrome - Yiwen Zhang; Youlu Shen (Journal of International Medical Research)
This article outlines a comprehensive analysis of the progress in the study of Wellens syndrome, which starts from a large body of relevant literature and systematically elaborates on the in-depth discussion, including the definition of the Wellens syndrome and the relationship between myocardial ischemia and coronary artery lesions. In terms of clinical manifestations, the characteristic electrocardiographic changes and related symptoms are described in detail. In terms of diagnostic methods, it ranges from the identification of electrocardiographic features to the combined use of myocardial marker testing and imaging. In conclusion, research on Wellens syndrome has further improved an understanding of its etiopathological mechanisms. This review aimed to clarify the nuances of Wellens syndrome and its impact on cardiovascular practice, raising awareness of at-risk populations and improving patient outcomes. It also provides a comprehensive and in-depth reference for the recognition, diagnosis, and treatment of Wellens syndrome to help clinicians fully understand and effectively diagnose and treat it.